Central Bank Involvement in Banking Crises in Latin America - Jacome, Luis (IMF Working Papers; Working Paper ;, 2008)
This paper reviews the nature of central bank involvement in 26 episodes of financial disturbance and crises in Latin America from the mid-1990s onwards. It finds that, except in a handful of cases, large amounts of central bank money were used to cope with large and small crises alike. Pouring central bank money into the financial system generally derailed monetary policy, fueled further macroeconomic unrest, and contributed to simultaneous currency crises, thereby aggravating financial instability. In contrast, when central bank money issuance was restricted and bank resolution was timely executed, financial disturbances were handled with less economic cost. However, this strategy worked provided appropriate institutional arrangements were in place, which highlights the importance of building a suitable framework for preventing and managing banking crises.